2019
DOI: 10.1002/psp.2270
|View full text |Cite
|
Sign up to set email alerts
|

Settlement intention of migrants in the Yangtze River Delta, China: The importance of city‐scale contextual effects

Abstract: Millions of Chinese migrants have moved from the countryside to cities to seek job opportunities and a better life. Under the policy shift from “land‐based urbanisation” to “people‐oriented urbanisation,” it is important to understand what determines migrants' settlement intentions. Although previous studies have primarily focused on sociodemographic impacts on settlement intention, the role of city‐level contexts is understudied. Drawing upon data, the 2015 Migrant Dynamic Monitoring Survey in the Yangtze Riv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 33 publications
3
35
0
Order By: Relevance
“…Following previous studies (e.g., Chen & Wang, 2019; Fan, 2011), respondents who chose “staying for more than 5 years” in the 2012 and 2014 surveys and those who chose “staying for 6 to 10 years” or “permanent settlement” in 2017 survey were categorised as having long‐term settlement intentions. Although previous research dropped the “uncertain” category or combined it with other categories (e.g., Cao et al, 2015; Dang, Chen, & Dong, 2019; Fan, 2011), we chose to retain it because uncertainty results from not knowing how regulations might affect employment prospects, a key theme of our research. Indeed, almost 25% of respondents chose “uncertain” (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Following previous studies (e.g., Chen & Wang, 2019; Fan, 2011), respondents who chose “staying for more than 5 years” in the 2012 and 2014 surveys and those who chose “staying for 6 to 10 years” or “permanent settlement” in 2017 survey were categorised as having long‐term settlement intentions. Although previous research dropped the “uncertain” category or combined it with other categories (e.g., Cao et al, 2015; Dang, Chen, & Dong, 2019; Fan, 2011), we chose to retain it because uncertainty results from not knowing how regulations might affect employment prospects, a key theme of our research. Indeed, almost 25% of respondents chose “uncertain” (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Given the hukou reform has taken place in mostly mid-and small-size destinations, it may be fruitful for researchers to consider the contextual impact of city-scale and to explore how city-scale may moderate the impact of social welfare insurance on settlement intentions (Dang, Chen, & Dong, 2019).…”
Section: The Heterogeneous Effects By Urban Residential Durationmentioning
confidence: 99%
“…Under this reform, hukou restrictions are to be abolished in small cities and towns, relaxed in medium‐sized cities, but tightly maintained in a handful of megacities (Xinhua, 2014). Given the hukou reform has taken place in mostly mid‐ and small‐size destinations, it may be fruitful for researchers to consider the contextual impact of city‐scale and to explore how city‐scale may moderate the impact of social welfare insurance on settlement intentions (Dang, Chen, & Dong, 2019).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…However, migrants with a higher educational attainment are more capable of integrating into and settling in the host city (Fan & Chen, 2012; Yang & Guo, 2018). Recent studies based on survey data collected in one or several cities have shown that an increasing number of migrants have an ambivalent identity, considering themselves as a part of the host society and that they are increasingly willing to settle permanently in the host city (Chen & Fan, 2018; Chen et al, 2020; Dang et al, 2019; Hao & Tang, 2018; Huang et al, 2018; Liu et al, 2016; Tang, 2019; Tang & Hao, 2019; Xie et al, 2017; Yang & Guo, 2018). However, despite a strong intention to settle in the host city, many migrants have few resources and are confronted with multiple constraints in the destination, which reduces their opportunity to integrate into the host society (Fan, 2011; Knight & Gunatilaka, 2010; Zhu, 2007; Zhu & Chen, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…They assumed that most migrant workers were satisfied with their socio‐economic status in the host city, as migrants' social identity remained rooted in sending communities, and their reference group for social comparison remained their relatives and friends in sending communities (Chan & Buckingham, 2008; Nielsen, Smyth, & Zhai, 2010; Zheng, Long, Fan, & Gu, 2009). More recent studies have shown that migrant workers were diversified in terms of social identity and settlement intention and that an increasing number of migrant workers had a local identity and were willing to settle permanently in the host city (Chen & Fan, 2018; Chen, Wang, Liu, & Liu, 2020; Dang, Chen, & Dong, 2019; Hao & Tang, 2018; Huang, Liu, Xue, Li, & Shi, 2018; Liu, Wang, & Chen, 2016; Tang, 2019; Tang & Hao, 2019; Xie, Wang, Chen, & Ritakallio, 2017; Yang & Guo, 2018). Some migrants, especially those who were born after 1980 (“new generation migrants”), tended to shift their reference group from sending communities to their peers in receiving communities over time, and they tended to suffer from a mismatch between rising aspirations for a better life and the realities of poor working and living conditions (Cheng, Wang, & Smyth, 2014; Huang et al, 2017; Jin, 2016; Knight & Gunatilaka, 2010).…”
Section: Introductionmentioning
confidence: 99%